In praise of plant pesticides - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A decade of research at the Lowlands Agricultural Experiment Station (LAES), the largest research station of the National Agricultural Research Institute (NARI), has led to the development and release of three plant derived pesticides (PDP).